Internal water pressure development in saturated concrete cylinder subjected to coefficient of thermal expansion tests: Poroelastic model. (1st June 2016) - Siddiqui, Md Sarwar; Grasley, Zachary; Fowler, David W.
Highlights: Quantify the internal water pressure development in a saturated CTE concrete sample. Numerical model is in good agreement with the experimental data. Predicted internal water pressure was high enough to potentially induce microcracking in concrete. This model helps to understand the effect of material properties on the measured CTE. Abstract: Coefficient of thermal expansion (CTE) test procedures use saturated concrete samples to (ostensibly) avoid the effect of moisture content. Concrete is a porous material, and internal water pressure develops in saturated concrete when subjected to temperature change due to the difference in CTE between liquid and solid phases. The measured CTE is affected by the internal water pressure development in saturated concrete samples. This paper represents an analytical model that was developed based on the poromechanical phenomenon of concrete to determine the time dependent internal water pressure and axial strain development. Material properties including, CTE, moduli of liquid and solid phase of concrete, as well as porosity and permeability of concrete samples have influence on the internal water pressure development. The predicted axial strain from the proposed numerical model for saturated concrete samples subjected to temperature changes were consistent with the experimental results. Predicted internal water pressure of the hardened concrete cylinder was as high as 700 psi (4.8 MPa), which is sufficiently high to potentially induce microcracking.